2017
DOI: 10.1016/j.celrep.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Proliferation and Apoptosis Maintain the Rapid Turnover of Microglia in the Adult Brain

Abstract: SummaryMicroglia play key roles in brain development, homeostasis, and function, and it is widely assumed that the adult population is long lived and maintained by self-renewal. However, the precise temporal and spatial dynamics of the microglial population are unknown. We show in mice and humans that the turnover of microglia is remarkably fast, allowing the whole population to be renewed several times during a lifetime. The number of microglial cells remains steady from late postnatal stages until aging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
551
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 554 publications
(583 citation statements)
references
References 48 publications
28
551
2
2
Order By: Relevance
“…These data estimate that it takes approximately 96 days to renew the entire microglial population in mice, suggesting several cycles of microglial self-renewal during a mouse's lifetime. The number of self-renewal cycles in the human brain was estimated to be around 100 (7). This striking difference between human and mouse supports the idea that rodent microglia may not experience pathological factors associated with aging such as senescence or dystrophy (70).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 64%
See 2 more Smart Citations
“…These data estimate that it takes approximately 96 days to renew the entire microglial population in mice, suggesting several cycles of microglial self-renewal during a mouse's lifetime. The number of self-renewal cycles in the human brain was estimated to be around 100 (7). This striking difference between human and mouse supports the idea that rodent microglia may not experience pathological factors associated with aging such as senescence or dystrophy (70).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 64%
“…Lawson and colleagues reported a microglial turnover rate of 0.05% at any given time in healthy brain (141), but recent data from the same group indicated a turnover rate of 0.69% (7). These data estimate that it takes approximately 96 days to renew the entire microglial population in mice, suggesting several cycles of microglial self-renewal during a mouse's lifetime.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 95%
See 1 more Smart Citation
“…In several studies it was suggested that microglial cells maintain their own population in the adult CNS via endogenous proliferation (20,27,28,84), but only a limited amount of experimental evidence supporting this hypothesis is available so far. A recent investigation revealed that microglial cell number is tightly controlled by temporal and spatial coupling of apoptosis and proliferation within the microglial population, which provides evidence for tight control of microglial cell numbers (85). Using a novel microglia-fate mapping system, it was shown that in the healthy brain regional differences in microglia self-renewal exist and that microglia expansion is a random process during homeostasis that can shift to clonality upon pathology (86).…”
Section: Physiological Function Of Microglia In the Adult Brainmentioning
confidence: 99%
“…Next to proliferation, microglial apoptosis contributes to maintaining the turnover of microglia in the adult CNS (Askew et al, 2017). A challenging central question is whether microglial self-renewal is the result of asymmetric cell division of microglial precursors in the CNS.…”
Section: Microglia Originmentioning
confidence: 99%